Knowledge, Attitudes And Behaviors of Primary Healthcare Physicians About Vaccines - Oguzoncul, A. Ferdane; Tuncer-Kara, Kevser; Deveci, S. Erhan (Doc Design Informatics Co Ltd, 2020)
Objective: The vaccine is a solution that stimulates the immune system in order to prevent diseases. This study aimed to investigate the knowledge, attitudes and behaviors of family physicians working in primary care about the vaccine. Methods: The population of this descriptive study consisted of family physicians working in Elazig provinces and districts. We reached 88.7% of family physicians. A questionnaire including demographic questions, 12 knowledge, 13 attitude and 5 behavior questions was applied to family physicians. The data were evaluated with SPSS 22 program. In statistical evaluations, Chi-square, Mann-Whitney U, Kruskal Wallis and Spearinan's correlation tests were used. Statistical significance was set as p<0. Results: Of the 165 family physicians participating in the study, 66.7% were male, and the mean age was 40.67 a, 8.85. The correct answer rate of the 13 questions about the knowledge was 7.59 +/- 2.17 on average. The flu vaccine, of which 15.8% of the participants had the most hesitation in administration, was the vaccine that 52.6% applied to themselves and their relatives most. 'there was no significant difference between the correct answers of those with and without children (p> 0.05). The attitude score was higher in married people than singles (p = 0.006) and people with children compared to those without children (p 0.012). The behavioral score of the 46-55 age group was higher than that of married people (p <0.001), those who had no children (p <0.001), and those who did research (p <0.001). A positive correlation was found between age and attitude (p 0.02) and behavioral score (p 0.03). There was no significant difference between the self-administered vaccine status and the number of correct answers (p> 0.05). Conclusions: We determined that family physicians who were primarily responsible for vaccination had misinformation about the vaccine, that the researchers' behavior score was high, and that age and attitude and behavior score were positively related.
Birinci basamakta çalışan hekimlerin aşılar hakkında bilgi, tutum ve davranışları
Keywords: Vaccine; family physician; knowledge; attitudes and behaviors